2009
DOI: 10.1007/s12648-009-0138-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on suitability of pure and α-Histidine doped KDP crystals in high speed applications

Abstract: Ferroelectric Potassium Dihydrogen Phosphate (KDP) crystals are widely used in modern short wavelength laser techniques, non-linear and integrated optics. The pure and -Histidine doped KDP crystals were procured from SRM Institute of Science and Technology, Chennai. The presence of additive in the doped KDP crystal is confirmed through X-Ray diffraction patterns and the lattice parameters were evaluated. Also, Fourier Transform Infrared spectrum confirms the presence of -Histidine in the doped crystals. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…In this sense, there are several studies in the literature dealing with the vibrational and NMR properties of the compound and of several of its molecular complexes. 3,[5][6][7][8][9][10][11][12][13] Surprisingly, most of these studies ignored the fact that the crystalline compound may exist in several polymorphic forms. Indeed, PZA was found to crystallize in at least four different polymorphs (R, , δ, γ; a fifth form, R′, very similar to form R, has also been proposed; see Figure 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, there are several studies in the literature dealing with the vibrational and NMR properties of the compound and of several of its molecular complexes. 3,[5][6][7][8][9][10][11][12][13] Surprisingly, most of these studies ignored the fact that the crystalline compound may exist in several polymorphic forms. Indeed, PZA was found to crystallize in at least four different polymorphs (R, , δ, γ; a fifth form, R′, very similar to form R, has also been proposed; see Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…For example, infrared or Raman data for the compound have been discussed in several of those studies 3,6,8,10,11,[28][29][30] without specification of which polymorph was under investigation. In a recent study, Castro et al 31 reported the infrared spectra of the different polymorphs of PZA, thus filling an important gap on the available knowledge about this compound.…”
Section: Introductionmentioning
confidence: 99%
“…The peak 2623 cm -1 are assigned to deformation N-C-H stretching, respectively. The nitrophenol group C-NO2 stretching and CH in plane bending occurs at 1165 cm -1 [19] and 1113 cm -1 [20], respectively. The peaks at 821, 754 and 703 cm -1 are assigned to in plane C-N-C, NO2 scissoring, in plane C-C-C bending.…”
Section: Ftirmentioning
confidence: 99%
“…Dopant is added to occupy the interstitial positions in the lattice and in turn this may lead to distinctive changes in the physical properties [3]. Inspite of having all good factors, the organic crystals could not be employed satisfactorily in devices because of their poor mechanical and thermal stability [4]. So, semi organic crystals having the properties of both inorganic and organic species, are expected to have good optical thermal and mechanical properties, Pooder [5] has reported that the addition of clove to KDP crystal enhances the second harmonic generation of KDP and also its mechanical strength.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%